Small fatigue crack growth behavior of TB6 titanium alloy - XU Liang; HUANG Shuang-jun; HUI Li; WANG Lei; ZHOU Song; ZHAO Qing (Cailiao gongcheng, 2019)
The growth behavior of naturally-initiated small cracks in single edge notched tensile (SENT) specimen of TB6 titanium alloy was studied. Fatigue experiments were conducted under constant amplitude loading with the stress ratios R of 0.1 and 0.5 at room temperature. Small cracks were allowed to be monitored by replica method during fatigue testing. Results show that at the same stress ratio, the initiation life of crack increases from 60% to 80% of the total fatigue life with the decrease of stress level. However, the stress level has no significant effect on the crack growth rate of TB6 titanium alloy. The crack growth rate at the early stage is greatly affected by the microstructure. Once the crack length reaches 200μm, the crack growth rate will increase rapidly regardless of grain boundary or grain orientation. Small cracks of TB6 titanium alloy are originated from the sample notch root in the form of corner crack, and the major part of total fatigue life is consumed in small fatigue crack initiation phase.